Evaluation of residual damage in felling gaps and extraction routes in single selection method (Siyahkal forest) - Ramin Naghdi; Nasrollah Rafatnia; Iraj Bagheri; Vahid Hemati (تحقیقات جنگل و صنوبر ایران, 2008)
Siyahkal forest in Guilan province consists of industrially valuable hardwood species such as Beech (fagus orientalis) and Hornbeam (Carpinus betulus), which have significant economic value. This research evaluated the damages caused by felling operation and log extractions in uneven aged hardwood forest of Siyahkal, where silvicultural selection method was practiced. In 31 felling gaps 113 trees were marked and felled and then examined. In this research the complete enumeration forest mensaration method was used to evaluate the amount of damages to forest stand in each felling stages and extraction stages from stump to side of skidding routes in felling gaps and load collection area. Weight averages was used in order to evaluate the overall damages in area of the study, because of differences in sizes of the felling gaps and extraction routes. The results of this study showed that the damages to forest stand in extraction routes were 42.5% where as in felling gaps were 17.5%.Assessment of the scars to tree trunks showed that the scars caused by extraction operation were bigger in size than felling operation. Also the scars were present more at height of two meters from ground level and were mostly deep scars i.e. damages to cambium. Analyzing the scars of forest stand in felling gaps showed that the damages increase with increase in intensity of harvesting.